Biomechanical and neuromuscular differences between the snatch and clean in elite weightlifters - Arauz, P. G.; Garcia, G.; Llerena, J.; Kao, I. (Journal of Biomechanics, 2026)
Despite fundamental biomechanical differences between the snatch and clean, few studies have systematically compared their mechanical and neuromuscular profiles in elite weightlifters, limiting evidence-based training and coaching strategies. This study examined full-body kinematics, vertical ground reaction forces, surface electromyography (EMG), and barbell kinematics in 10 elite athletes performing lifts at 80 % of their competition maximum. Consistent with our hypothesis, the clean exhibited a force-dominant profile, characterized by higher vertical ground reaction forces across most lift phases (e.g., 904.2 ± 99.72 N vs. 842.81 ± 109.32 N at the end of the first pull, p < 0.001), greater EMG activity in the biceps femoris, gastrocnemius, vastus lateralis, and gluteus during key phases (p < 0.05), and reduced vertical bar displacement (1.08 ± 0.06 m vs. 1.29 ± 0.06 m, p < 0.001), reflecting its emphasis on efficient load transfer and postural control during the catch. In contrast, the snatch demonstrated a velocity- and technique-dominant profile, with higher bar velocities (e.g., 2.06 ± 0.16 m/s vs. 1.58 ± 0.19 m/s at the end of the second pull, p < 0.001), greater hip and knee flexion and abduction, and pronounced external rotation of the hip and shoulder during early and terminal phases of the lift, respectively (p < 0.05). These findings emphasize the snatch`s reliance on rapid bar acceleration, technical precision, and precise intersegmental coordination. The snatch`s longer bar path and wider grip (1 ± 0.05 m vs. 0.58 ± 0.05 m, p < 0.001), further underscore its dependence on mobility, neuromuscular timing, and technical proficiency rather than maximal force output. These lift-specific biomechanical signatures provide a foundation for optimizing strength and power development, refining technical coaching cues, and informing injury-prevention strategies in high-performance weightlifting.